Pengaruh durasi pembakaran dan persentase abu sekam padi terhadap kuat tekan mortar - Masruri, Mochamad Hafidh; Trimurtiningrum, Retno; Rochmah, Nurul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Cement is one of the main materials in mortar that has a negative impact due to its manufacture. Various new studies and innovations continue to be carried out to increase the utility value of waste and reduce the negative impacts of cement manufacture. One of the innovations is the use of rice husk ash as a substitute for cement in making mortar. It is known that rice husk ash has a high silica content where the content is the same as the content of cement. The duration of good burning of rice husk ash is 6 hours with normal burning. The percentage of rice husk ash used in the study was 0%, 5%, 10%, and 15% of the weight of cement. The test results showed that 10% rice husk ash with a burning duration of 6 hours used as a mortar mixture had the highest compressive strength value of 32.04 MPa.